One year of hyperglycemia in the Ins2Akita mouse does not impart changes in retinal vascular patterning - Fei Shang; Kosha Dholakia; Jesse Schallek (PLoS ONE, 2026)
Diabetic retinopathy (DR) is one of the leading causes of blindness often associated with retinal vascular pathology in humans. To aid our understanding of DR, the Ins2 Akita mouse has served as a type 1 diabetes model. These mice have sustained elevated blood glucose (BG) and we tracked microvascular changes in the retinal circulation for up to one year. Retinal flat mounts of male Ins2 Akita x NG2DSRed (n = 14) mice age 7–61 weeks were imaged using a confocal microscope and compared to age matched euglycemic mice (n = 13) to establish a ground-truth of vascular patterning. We analyzed vessel density, vessel branching, vessel length, tortuosity, pericyte density, and the connectivity between vascular plexuses at eccentricities up to 2 mm from the optic disc. An additional hyperglycemic mouse was longitudinally imaged using an adaptive optics scanning light ophthalmoscope (AOSLO) for 12 weeks from 24–36 weeks of age. We found that up to one year of hyperglycemia had minimal impact on these retinal vasculature metrics that are also accessible to in vivo ophthalmoscopy. The longitudinally imaged mouse showed no changes and high congruence with ex vivo data. We conclude that yearlong elevated blood glucose did not impart detectable changes in retinal microvascular patterning.